(3cJGH eaJGM GdWHs - (3CHh GdaQL gfOhs ((3eMeO Hf eMeO GdbhUhi s)
(3ChdgG (B:s
(3bGd JUaM CNhGffG ef GdeJYdejf ebGdJi GdehSheI HGdeThbI ai GdeONd Edi Yde GdadSaI aThbJge HSghdI GdeiNP ajgG Edi ebGdI ai GdWH s
(3BNQgG (B:s
(3hjbGd Gdjhe GdPi ajg jchf GdHMQGf jhe HGMhQi hdG jbGd HMQGfi CjgG GdCNhGf gPg NGJeI cJGH GdeaJGM s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1762s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs